Effect of Unified Power Quality Conditioner on Voltage and Current Waveforms - MAHMOUD, Muhammad Ossama; MAMDOUH, Wael; KHALIL, Hamdy (Walailak Journal of Science and Technology (WJST), 2021)
Power quality improvement faces different and significant problems due to voltage instability and the wide use of electronic power devices. To overcome these different power quality problems, an active power filter is used. The active power filter, in general, has 4 main categories- shunt, series, unified power quality conditioner, and hybrid active power filter. The shunt active power filter is usually used to mitigate source current harmonics and compensate reactive power for power factor correction. The series active power filter is usually used to mitigate voltage problems (sags, swells, transients, dips, distortions, harmonics, etc.). The unified power quality conditioner is a combination of the shunt active power filter and the series active power filter; it is used to mitigate all voltage and current problems, compensate voltage, current system harmonics, and reactive power compensation, and mitigate voltage dips, voltage sags, voltage swells, and voltage phase shift. In this paper, the 3-phase 3-wire unified power quality conditioner is utilized to mitigate all power system problems (voltages and currents) and discuss the effect of the shunt and series active power filter separately on source voltage and source current waveforms. This case study shows that the source voltage distortion can be mitigated by using the series active power filter alone, but the source current distortion cannot be mitigated without using both the series and shunt active power filter. The source current harmonic problem mainly exists due to 1) distorted voltage sources, and 2) non-linear loads. Therefore, the unified power quality conditioner must be used to mitigate source current distortions in the case of the distorted voltage source, to comply with the standard limits IEEE 519, IEC 555, and IEC 61000. HIGHLIGHTS The UPQC is used to mitigate all voltage and current problems and improve all power system quality The SEAPF eliminates all voltage problems The SHAPF has no effect on source voltage The SHAPF eliminates source current harmonic distortion GRAPHICAL ABSTRACT